Kajian Teoritis Dan Empiris Mengenai Penggunaan Biaya Relevan Dalam Proses Pengambilan Keputusan Manajerial - Indah Simanjuntak; Nazla Alifia Putri Hadi; Winona Keysadli (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
A shortterm decision that demands the use of relevant costs, future costs that differ between alternatives, in order not to be trapped in total costs or sunk costs that can be misleading [1]. Various empirical studies show that relevant costs improve the quality of decisions such as special orders, make-or-buy, and asset replacement; in SMEs, this analysis has been proven to help choose the most cost-effective option, such as at Anna Bakery and UMKM Roti Hangat Keliling which determine special order decisions and oven use based on relevant cost calculations [2]. However, the effectiveness of relevant costs does not only depend on mathematical calculations, but is also influenced by cognitive biases such as framing bias, the quality of management accounting systems, managers' thinking styles, as well as organizational factors and non-financial values, so that its application is a combination of data, context, and decision-maker behavior [4].